Comparative studies on physicochemical properties, volatile flavor substances and microbial community of Mianning ham at different altitudes - Zeng, Qianhui; Ji, Lili; Wang, Wei; Zhang, Jiamin; Bai, Ting; Gan, Ling; Chen, Lin (Frontiers in Microbiology, 2025)
BackgroundThis study explores the impact of varying altitudes on the quality characteristics of Mianning ham.MethodsBy utilizing Solid-Phase Microextraction—Gas Chromatography–Mass Spectrometry (SPME-GC-MS) technology and high-throughput sequencing techniques, the physicochemical properties, volatile flavor compounds, and shifts in microbial communities of Mianning ham at different altitudes were investigated.ResultsHam’s water content, aw, pH, malondialdehyde content,and nitrite content at high altitudes were higher, while the salt content of ham at low altitudes was higher. 112 volatile compounds were identified in ham fermented for 0, 1, and 2 years at low altitude and high altitude, and the volatile compounds in ham at high altitude were more abundant than those in ham at low altitude. The main flavor compounds were 1-octene-3-ol, Nonyl aldehyde, Octanal, and 15 other volatile compounds. At the phylum level, the dominant bacteria were Firmicutes and Proteobacteria, and the fungus was Basidiomycota. Staphylococcus was the dominant bacterium at the genus level, and Aspergillus was the dominant fungus.The correlation analysis of microorganisms and volatile flavor substances showed that Cobetia promoted the formation of Benzaldehyde in ham at low altitudes. In contrast, Kocuria promoted the formation of 1-Octanol, Heptanol,1-Butanol, 2-Heptanone, 3-Hydroxy-2-butanone, Octanal, and Hexanal in ham at high altitudes.DiscussionThere were obvious differences in the quality of Mianning ham between the two altitudes.